Sales force compensation and incentive schemes: Practices in the South African pharmaceutical industry - Russell Abratt; Manfred Klein (South African Journal of Business Management, 1999)
Compensation plans that incorporate incentive schemes act as a sales force motivator. This study deals with sales force compensation plans from a management perspective, in the South African pharmaceutical industry. A literature review of incentive schemes is provided. Results are reported about the compensation plans and incentive schemes of 38 organisations. The design, implementation, and evaluation of sales force compensation and incentive schemes are discussed. Guidelines for the development of sales force incentive schemes are provided.
Keywords: 650